Inter-Professional Collaboration: Enhancing Patient Care Through Doctor-Nurse Partnerships (Journal of Namibian Studies : History Politics Culture, 2023)
Inter-professional collaboration between doctors and nurses is essential for delivering high-quality patient care in modern healthcare settings. This collaboration involves the integration of medical expertise and nursing care to provide comprehensive, patient-centered services. Clear communication, mutual respect, shared decision-making, and defined roles are crucial elements of effective doctor-nurse partnerships. While challenges such as hierarchical structures and role ambiguity exist, proactive strategies can overcome these barriers. Successful collaborations result in improved patient outcomes, enhanced care quality, and increased professional satisfaction. This abstract highlights the significance of doctor-nurse partnerships and offers insights into best practices for fostering collaboration in healthcare organizations.